Risks and Challenges for Thai Exporters in 2024 Case Study: Exporters of Textiles and Garments, Processed Food and Beverages - จันทรโพธิ์ศรี, อารีรัตน์; น้อยโสภา, สุณัฐวีย์; เพชรโสม, ณัฐวดี (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to 1) study the risks and challenges faced by international exporters in the textiles and garments group, and the processed food and beverage group, occurring in year 2024, 2) investigate risk management strategies for international exporters. This research utilized a qualitative methodology through document collection, literature review, and in-depth interviews with exporters in the textile and apparel sector, as well as the processed food and beverage sector. The study also involved interviewing experts with experience in export businesses. The research findings show that the risks and challenges faced by Thai exporters in 2024 consist of 7 main factors: 1) financial risks, including fluctuations in foreign exchange rates, 2) the domestic and global economic conditions, 3) laws and regulations related to international trade, 4) emerging infectious diseases, 5) logistics and international transportation systems, 6) technology systems supporting operations, and 7) natural disasters. The interview results with exporters are consistent with the document and research findings. All these factors have a negative impact on exporters, from planning operations to costs, delivery times, payment collection, and competitiveness. Therefore, exporters need to develop risk prevention strategies against various factors to survive and remain competitive in the global market.